THE MEDIATING EFFECT OF ORGANIZATIONAL AGILITY ON THE RELATIONSHIP BETWEEN ELECTRONIC HUMAN RESOURCE MANAGEMENT AND ORGANIZATIONAL PERFORMANCE OF E-COMMERCE BUSINESS IN BANGKOK - Panyindee , Janjirapon; Panyindee, Somporn; Kongsatitporn, Prapasara (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
The objectives of this research were to 1) investigate electronic human resource management affecting organizational performance, 2) examine organizational agility affecting organizational performance, 3) analyze electronic human resource management affecting organizational agility, and 4) assess the effect of organizational agility on the relationship between electronic human resource management and organizational performance of e-commerce businesses in Bangkok. The research was quantitative. A questionnaire was used to collect data from 280 executives of e-commerce businesses in Bangkok. Data analysis employed descriptive statistics, including mean and standard deviation, as well as inferential statistics, such as Pearson correlation and multiple regression. The research results indicated as follows; 1) The mean of electronic human resource management was at a high level. The mean organizational agility was at a high level. The mean organizational performance was at a high level. 2) Electronic human resource management had a positive effect on organizational performance with statistical significance at the 0.01 level. Organizational agility had a positive effect on organizational performance with statistical significance at the 0.01 level. Electronic human resource management had a positive effect on organizational agility with statistical significance at the 0.01 level. 3) Organizational agility partially mediated the relationship between electronic human resource management and organizational performance of e-commerce businesses in Bangkok. The findings of this study can support decision-making regarding investment in electronic human resource management systems to increase organizational agility and enhance organizational performance. Additionally, this study contributes academic value by confirming the mediating role of organizational agility.